Strategy to Induce Multiferroic Property in (RTiO3)n/(RVO3)n Superlattices: A First‐Principles Study1. Issue 9 (8th April 2019) - Yao, Fen; Meng, Junling; Zhang, Lifang; Liu, Xiaojuan; Meng, Jian; Zhang, Hongjie
Abstract: By first‐principles calculations, lanthanide contraction is applied on a 1/1 (with symmetric center) and a 2/2 (with non‐centrosymmetric polar structure) RTiO3 /RVO3 superlattices to realize quasi‐continuous structural distortion modulation. The strong correlations of microscopic structural distortion, magnetic coupling and charge disproportionation accompanying metal‐insulator transition (MIT) are clarified. It is found that the effect of lanthanide contraction on the 1/1 and 2/2 RTiO3 /RVO3 superlattices can induce ferromagnetic to antiferromagnetic transition within ab VO2 plane and the MIT occurs within these superlattices. And the MIT phenomenon is attributed to the charge disproportionation on V sites caused by the magnetic coupling transition. More structural distortion in the 2/2 RTiO3 /RVO3 superlattice is necessary than that of the 1/1 RTiO3 /RVO3 superlattice to induce the similar magnetic and MIT transition originating from the smaller interface/volume ratio. Based on these results, combining lanthanide contraction and epitaxial strain effects, multiferroic property is realized on 2/2 YTiO3 /YVO3 superlattice. Among all the structural parameters, aspect ratio c/a and Ti−O−V bond angles along the [001] direction are found to play the vital roles in the relevant transition process. Therefore, our calculations provide a microscopic guidance to design and synthesize new multiferroic materials. Abstract : The strong correlations between microscopic structural distortion, magnetic coupling, and charge disproportionation accompanying metal–insulator transitions are clarified in (RTiO3 )n /(RVO3 )n (R=rare earth, n=1 or 2) materials by using first‐principles calculations. The study provides a microscopic guidance to design and synthesize new multiferroic materials.